Technical analysis and applications with MATLAB - Stanley, William D. (Thomson Delmar Learning, 2005)
This text combines technical and engineering mathematical concepts at a basic level using MATLAB® for support and analysis. Once math concepts are introduced and understood using conventional techniques, MATLAB® is then used as the primary tool for performing mathematical analysis. Featuring practical technical examples and problems, the text is designed for math courses within an engineering technology or engineering program or any courses where MATLAB is used as a supporting tool. The text provides a review of differential and integral calculus with an emphasis on applications to technical problems.